Does Lean implementation interact with group functioning?. Issue 2 (13th May 2014) - Ulhassan, Waqar; Westerlund, Hugo; Thor, Johan; Sandahl, Christer; von Thiele Schwarz, Ulrica
Abstract : Purpose: – As healthcare often is studied in relation to operational rather than socio-technical aspects of Lean such as teamwork, the purpose of this paper is to explore how a Swedish hospital Lean intervention was related to changes in teamwork over time. Design/methodology/approach: – Teamwork was measured with the Group Development Questionnaire (GDQ) employee survey during Lean implementation at three units, in 2010 ( n =133) and 2011 ( n =130). Qualitative data including interviews, observations and document analysis were used to characterize the Lean implementation and context. The expected teamwork change patterns were compared with GDQ data through linear regression analysis. Findings: – At Ward-I, Lean implementation was successful and teamwork improved. At Ward-II, Lean was partially implemented and teamwork improved slightly, while both Lean and teamwork deteriorated at the emergency department (ED). The regression analysis was significant at ED ( p =0.02) and the Ward-II ( p =0.04), but not at Ward-I ( p =0.11). Research limitations/implications: – Expected changes in teamwork informed by theory and qualitative data may make it possible to detect the results of a complex change. Practical implications: – Overall, Lean may have some impact on teamwork, if properly implemented. However, this impact may be more prominent in relation to structural and productivity issues of teamwork than group members' relational issues. Practitioners should note that, with groups struggling with initial stages of group functioning, Lean may be very challenging. Originality/value: – This study focussed specifically on implications of Lean for nurse teamwork in a hospital setting using both qualitative and quantitative data. Importantly, the group functioning at the time when Lean is initiated may affect the implementation of Lean.